Possum's cinematic space: Landscape, alienation and New Zealand Gothic. Issue 1 (1st April 2016) - Leotta, Alfio
Possum has often been read as a commentary on the sense of place and belonging in postcolonial New Zealand. This article proposes a semiotic analysis of the construction of space in Possum. In particular, it will examine the stylistic choices deployed by the director in relation to the notions of alienation and New Zealand Gothic.